Caregiver's perceptions of attachment and behaviors exhibited by institutionalised children: the Zimbabwean experience - Muguwe, Emely (International Research Journals, 2016)
The study sought to investigate perceptions of caregivers on attachment and behaviors exhibited by institutionalised children. The sample consisted of nine caregivers, purposively selected from three identified registered children’s institutions. Three caregivers were selected from each institution following set criteria. The study employed a qualitative research design and data were collected through the use of semi- structured interview schedules. The results revealed a number of emergent themes. Caregivers worked for long hours. The ratio of children to caregiver is too high in most cases. Psychological needs of children for proper attachment and positive care was being compromised. Children had mixed feelings about caregivers which indicated attachment behavior problems. Younger children adjusted to institutional care much faster than older children. A wide range of behavioral problems were noted, with detrimental consequences in some cases. The study recommended reduction of child-caregiver ratio and employment of additional staff. Training workshops should be held regularly to keep caregivers abreast of the requirements of childcare. There is need to channel some funds from the AIDS levy to children’s institutions.